1984
DOI: 10.1099/0022-1317-65-2-281
|View full text |Cite
|
Sign up to set email alerts
|

Cassia Yellow Blotch Virus: a New Bromovirus from an Australian Native Legume, Cassia pleurocarpa

Abstract: SUMMARY Cassia yellow blotch virus (CYBV) is a previously undescribed bromovirus infectingthe Australian indigenous legume, Cassia pleurocarpa, in western Queensland.Although CYBV infected test plants in several families, symptoms were usually restricted to local lesions on the inoculated leaves. Systemic infection occurred in only eight leguminous species and in the non-legume, Nicotiana clevelandii. Chenopodium amaranticolor was a suitable host for local lesion assays and CYBV was readily purified from N. cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Cassia yellow blotch bromovirus was first identified and found to infect Florida beggarweed in Australia. Hosts of this bromovirus include corn, cucumber (Cucumis sativus L.), dry bean, and soybean (Brunt et al 1999;Dale et al 1984). Nonsusceptible hosts include barley (Hordeum vulgare L.), jimsonweed, oat (Avena sativa L.), pea (Pisum sativum L.), peanut, pigeon pea [Cajanus cajun (L.) Millsp.…”
Section: Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassia yellow blotch bromovirus was first identified and found to infect Florida beggarweed in Australia. Hosts of this bromovirus include corn, cucumber (Cucumis sativus L.), dry bean, and soybean (Brunt et al 1999;Dale et al 1984). Nonsusceptible hosts include barley (Hordeum vulgare L.), jimsonweed, oat (Avena sativa L.), pea (Pisum sativum L.), peanut, pigeon pea [Cajanus cajun (L.) Millsp.…”
Section: Pathogensmentioning
confidence: 99%
“…], sorghum [Sorghum bicolor (L.) Moench. ], and sunflower (Helianthus annuus L.) (Brunt et al 1999;Dale et al 1984). Johnson et al (1996) found that Florida beggarweed was susceptible to tomato spotted wilt tospovirus (TSWV) but was not a preferred host for thrips (Frankliniella spp.)…”
Section: Pathogensmentioning
confidence: 99%
“…pleurocarpa is a bush-like plant including branched green leaves and bright colored flowers, wildly grown in the northern Australia (Dale, Gibbs, & Behncken, 1984). The seed endosperm of C. pleurocarpa is also a source of non-ionic water soluble galactomannan composed of D-galactose and D-mannose in the molar ratio of 1.00:2.01 (Singh et al, 2009a).…”
Section: Chemical Namementioning
confidence: 98%
“…In this study, we report on the structure and properties of the seed gum extracted from Cassia pleurocarpa, a bush-like plant with branched green leaves and bright colored flowers, found distributed in the northern Australia [20]. In order to explore the potential applications of the galactomannan isolated from C. pleurocarpa, the structural elucidation, rheological properties, water/saline retention, gelling behavior, and shelf life of the galactomannan were extensively studied and discussed.…”
Section: Introductionmentioning
confidence: 99%